SPECIAL ASPECTS OF THE TRANSVERSE KERR EFFECT WITH CONSIDERATION OF THE SIZE EFFECT IN NANO-COMPOSITES AS EXEMPLIFIED BY CoFeB - A. N. Yurasov; N. V. Granovsky (Российский технологический журнал)
The article deals with the analysis of the properties of nanocomposites as exemplified by CoFeB using the transverse Kerr effect (TKE). This nanocomposite has strong magnetic properties. It shows such effects as anomalous Hall effect and significant magneto-optical activity, which is of both fundamental and practical interest. In this article, in addition to calculating the optimal values in the modeling of nanocomposites, the possibility of their very wide application in a variety of fields is considered: from medicine and chemistry to the building industry, rocket engineering and aircraft construction. An important task is to study the structure of nanocomposites, which allows producing magneto-optical devices. The method of obtaining the CoFeB nanocomposite is described. The specific features of its magneto-optical spectra are explained in view of the results of the experiment in the framework of the effective medium theory and the size effect. Using the CoFeB nanocomposite this article allows explaining the value of the TKE, the spectra of which change their sign in the near IR region and, significantly, their shape. This behavior can be explained only by particle size distribution, i.e., size effect. The obtained results allow explaining experimental optical and magneto-optical spectra in nanocomposites, mainly, in the near and visible IR region. This article deals with the research on the optimal values of the parameters describing the nanocomposite. The following parameters of the nanocomposite were considered during the simulation: particle size, form-factor and light incidence angle. Fixing all the chosen parameters except the changeable one and carrying out corresponding calculations the author has succeeded in obtaining several different values describing the transverse Kerr effect influence on the nanocomposite. The importance of considering the size effect in the near IR region of the spectra is explained in the article. The description of the optical and magnetooptical spectra of the nanocomposite (CoFeB) is provided. Spectral dependences of the TKE were obtained, which allowed clearly demonstrating the change in signs and values of the effect in the near IR region. The size effect in the near IR region of the spectrum is associated with interband transitions.